Public-Private Partnership As the Instrument of Reforming of the Industrial Sector of the Economy - Khodiakova, Kateryna (Pressing Problems of Public Administration, 2019)
In the context of globalization and the prospects for the development of innovation systems, the modernization of modern industry becomes a priority in state policy in the context of managing the country’s economic system. At that time, an important tool of public administration becomes the improving of the relationship and interaction of the state and business, implemented in the form of public-private partnership. The questions of using of PPP mechanisms in various sectors are discussed in the works of P. Brusser V. Varnavsky, Y. Kindzersky A. Nikitaeva, S. Rozhkova, as well as in world researches M. Gerrard, A. Hauck, I. Mahdi, M. Rahman, F. Yasamis. The paper objective is to identify possible directions and mechanisms of using public-private partnership in the reform of the industrial sphere in order to solve the issues of modernization and optimization of the technological potential of the country. It is advisable to build such model of the industrial sector’s modernization of the industrial sector of the economy in which the state will play a leading role, but to act in cooperation with society and business. Moreover the main hopes for the construction of an innovative economy are connected with business. The PPP mechanism is often viewed as the so-called “semi-privatization”. Such interaction will achieve a synergistic effect and increase the ef ciency of the potential available to society. This gives grounds for considering the PPP as an intermediate form between state and private property, as well as a peculiar management alternative to privatization. To date, the potential of PPP projects in industry has not been used. Property industrial complexes should be included in the list of PPP objects and  xed at the legislative level. In today’s Ukrainian economy, there are many barriers (institutional, administrative, political, organizational and managerial) that prevent the involvement of private partners, especially foreign ones, and the implementation of PPP projects in general. In order to modernize the industrial sector with the use of PPP projects, it is now important to take into account the overall  nancial and economic situation in Ukraine and in the world. As experts point out, the relevance of the use of the mechanism of public-private partnership for modernization under unstable conditions is not diminishing, the PPP’s potential in this area, but it is expected to undergo signi cant structural changes. World experience has accumulated many forms and mechanisms for the implementation of PPP projects, including in the real sector of the economy. On the one hand it is necessary to intensify the practical implementation of the declared projects and move towards a wider application of PPP. On the other hand, institutional and economic conditions for cooperation between public and private structures should be developed. The direction of further research is developing a methodology for the formation of PPP projects and indicators for assessing the effectiveness of these projects in the industrial sector.